FORMATION OF MAJOR SUBJECT COMPETENCY OF FUTURE PRIMARY SCHOOL TEACHERS - Aryna L. Frumkina (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2020)
The article deals with the problem of the formation of major subject competency of future primary school teachers to teach fine arts in a foreign language. The research methods used during the work were the following: analysis of pedagogical, psychological, didactic literature on the research problem, which allows us to carry out a theoretical substantiation for the feasibility of forming a major subject competency of future primary school teachers to teach fine arts in a foreign language; modeling the educational process. The essence of the major subject competency of future primary school teachers, as well as its components such as: artistic and visual competency within the discipline “Fine Arts” which includes: historical and artistic, genre and artistic, technical and graphic competences, and foreign language and speech competency within the discipline “Foreign language” which embraces linguistic competence and speech competence, have been determined. A model of the process of the formation of the major subject competency of future primary school teachers to teach such a compulsory school subject as fine arts in a foreign language has been elaborated. The model includes 5 stages: motivational, which is carried out by means of a foreign language; receptive, which consists in presenting students with a new thematic material in the form of lectures; reproductive, which consists in the development of skills to retell the previously listened to lecture material in the oral and written forms; productive, which consists in teaching students: to discuss the contents of the lecture, to interpret and express their points of view regarding the content of the lecture, to expand independently its content and make a presentation; reflective and creative, which consists in the development of skills of practical application of the acquired knowledge in a foreign language